Responses of fresh concrete piles induced by pipe pile casing penetration in clay. Issue 1 (14th February 2020) - Ye, Mingge; Dong, Jinmei; Zhou, Mi; Zhou, Xiaowen; Lu, Xiaochun
Abstract : An extensive investigation into the responses of a fresh concrete pipe pile induced by the adjacent penetration of a pipe pile casing into clay, undertaken through large-deformation finite-element analysis, is described in this paper. The numerical model was validated using field monitoring and centrifuge test data in terms of penetration resistance and soil deformation, and good agreement was obtained. An extensive parametric study was conducted encompassing the practical range of relevant parameters, including penetration depth, soil properties, the distance between the casing and the fresh concrete pile, casing diameter, soil layer thickness and roughness. A formula for estimating the maximum lateral deformation of a fresh concrete pile was developed to provide guidance for practical pipe pile design.